A thematic analysis of messages posted by moderators within health-related asynchronous online support forums - Smedley, Richard M.; Coulson, Neil S. (Elsevier, 2017)
Objective: To identify and describe the activities performed by online support community moderators. Methods: A total of 790 messages were downloaded for analysis. Messages were written by 59 moderators from 6 forums that represent a diverse range of conditions (arthritis, complex regional pain syndrome, Crohn’s disease, depression, diabetes and Huntington’s disease). Results:Thematic analysis revealed four themes: supportive tasks supportive tasks involve providing help to members, moderators sharing experiences shows how they use forums to fulfil their own personal support needs, making announcements about new discoveries and upcoming events, and administrative tasks such as enforcing rules and deleting spam. Conclusion: These results are consistent with the helper-therapy principle and provide a new insight into the diverse and varied range of activities carried out by moderators. Practice implications: Moderators perform many roles, including using forums for their own support needs.